IMPLEMENTATION OF RELIGIUSITY AND LOCAL FUNCTION IN DEVELOPMENT OF OFFICE HUMAN RESOURCES MINISTRY OF RELIGION PALOPO CITY - Jabani, Muzayyanah; Takdir, Takdir (Nurani, 2020)
This study aims to determine whether the religiosity variable that focuses on the dimension of worship practices by discussing two aspects in it, namely obedience and rituals and local wisdom which consists of the culture of "sipakatau", "sipakalebbi" and "sipakainge" have an influence on human resource development, also researching about the practices of worship that have been carried out by employees of the Ministry of Religion Office of the City of Palopo and how the implementation of local wisdom is meant in the development of human resources. This research is descriptive quantitative research using data collection techniques by distributing questionnaires, interviews and literature. The analysis technique used with multiple linear regression analysis. The results of the study show that the form of religious activity as a form of religiosity that has been carried out in the office of the Ministry of Religion of Palopo City has 2 main things, namely relating to ritual and strictness as a form of the dimensions of religious practice. Both of these aspects, namely the ritual aspects and obedience aspects in general, have been carried out and carried out at the office of the Ministry of Religion in the city of Palopo. Keywords: religiosity, local wisdom, Human Resources Ministry